Enhancing Student Learning Through Parental Participation in School Meetings: A Case Study of Secondary Schools in Kinondoni Municipality,Tanzania - Pendo A. Byejwe; Prospery M. Mwila (Action Research Journal Indonesia (ARJI), 2025)
This study investigates the role of parental participation in school meetings in enhancing student learning in secondary schools in Kinondoni Municipality, Tanzania. The research aims to assess the level of parental involvement in school meetings, examine the impact of such participation on students’ learning, and identify strategies to improve engagement for better academic outcomes. A mixed-methods approach with a descriptive case study design was employed. The study involved 96 participants including one District Secondary Education Officer (DSEO), one Ward Education Officer (WEO),four secondary school heads, 26 teachers, 32 parents, and 32 students from four secondary schools in the municipality. Data were collected through structured questionnaires, semi-structured interviews, and documentary reviews. The findings revealed that parental participation in school meetings varied across schools, with some schools showing higher engagement due to effective communication strategies. Increased participation was linked to improved academic performance and greater collaboration between parents and teachers. Barriers to participation, such as time constraints and lack of awareness, were identified. The study recommends improving communication with parents, offering flexible meeting times, and implementing policies to encourage greater involvement.